Book of a thousand days - Hale, Shannon (Bloomsbury ; Distributed to the trade by Holtzbrinck Publishers, 2007)
Fifteen-year-old Dashti, sworn to obey her sixteen-year-old mistress, the Lady Saren, shares Saren's years of punishment locked in a tower, then brings her safely to the lands of her true love, where both must hide who they are as they work as kitchen maids.